Modified para-aramid paper and preparation method and product thereof
By modifying heterocyclic polyamide on aramid paper, the problem of insufficient agglomeration and binding force in water is solved, significantly improving the uniformity and mechanical properties of the paper, while maintaining heat resistance and flame retardant properties.
Patent Information
- Application Number
- CN202310430881.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-04-20
AI Technical Summary
The existing para-aramid paper has hydrophobic, smooth and high inertia on the surface of the fibers, which makes the fibers prone to agglomeration in water and difficult to disperse evenly, which reduces the uniformity of the paper, and the bonding force between the fibers is weak, so its mechanical properties cannot be effectively exerted.
By modifying para-aramid paper with heterocyclic polyamide, the heterocyclic polyamide has good film forming properties and can be dispersed in the fiber nonwoven fabric of para-aramid fiber, strengthening interfacial bonds between fibers, reducing porosity, and improving paper uniformity.
The mechanical properties of para-aramid paper are significantly improved, including tensile strength and interlayer peel strength, while maintaining good heat resistance and flame retardant properties.
Smart Images

Figure CN116695482B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of polymer materials, and in particular to a modified para-aramid paper and a preparation method and product thereof. Background Art
[0002] Para-aramid paper, made from para-aramid fiber through papermaking process, is a high-performance composite material with high strength, high modulus, light weight, high temperature resistance, flame retardancy, corrosion resistance, insulation and excellent wave transmission performance. It is widely used in high-tech fields such as aerospace, rail transportation, electronics and electrical, national defense and military industry. It can be used as a structural material in the form of honeycombs and laminates for high-rigidity secondary load-bearing structural components of aircraft, ships, high-speed railways, etc. It can also be used as a high-grade insulating material in generators, motors, transformers, and can also be used as battery separators, printed circuit boards, etc.
[0003] However, since the molecular chain of poly(p-phenylene terephthalamide) (PPTA) that makes up para-aramid is a rigid structure, the fiber surface is hydrophobic, smooth and highly inert, which causes para-aramid fiber and its differentiated products (short fibers, pulp and precipitated fibers) to easily agglomerate in water and is difficult to disperse evenly, reducing the uniformity of para-aramid paper. In addition, the smooth and inert surface makes the bonding force between fibers very weak, and the advantage of the excellent mechanical properties of para-aramid cannot be brought into play.
[0004] Therefore, it is necessary to improve the mechanical properties of para-aramid paper. Summary of the invention
[0005] The present application provides a modified para-aramid paper and a preparation method and product thereof, aiming to modify the para-aramid paper by using heterocyclic polyamide to obtain the modified para-aramid paper with good mechanical properties.
[0006] In a first aspect, the present application provides a modified para-aramid paper, comprising: a para-aramid paper substrate, comprising a fiber non-woven fabric formed by para-aramid fibers entangled with each other or bonded based on non-covalent forces; and a heterocyclic polyamide dispersed in the fiber non-woven fabric of the para-aramid fibers.
[0007] According to the present application, the para-aramid paper substrate is modified by using heterocyclic polyamide, which has good film-forming properties and can be dispersed in the fiber non-woven fabric of para-aramid fibers. The heterocyclic polyamide can enhance the interfacial bonding between the para-aramid fibers, thereby better transferring the stress, and can greatly reduce the porosity of the para-aramid paper, thereby significantly improving the uniformity of the para-aramid paper, and obtaining a modified para-aramid paper with good mechanical properties.
[0008] In some embodiments, in the modified para-aramid paper, at least a portion of the molecular chains of the heterocyclic polyamide pass through the pores in the nonwoven fabric of the para-aramid fibers to form a continuous network reinforcement structure.
[0009] In some embodiments, the heterocyclic polyamide is obtained by polymerization of a diamine monomer and a diacyl chloride monomer, wherein the diamine monomer includes a first diamine monomer and a second diamine monomer, the first diamine monomer is a heterocyclic diamine, and the second diamine monomer is an aromatic ring diamine.
[0010] In some embodiments, the modified para-aramid paper satisfies at least one of the following conditions: 1) the air permeability of the modified para-aramid paper is <0.001 μm / (Pa·s); 2) the thermal decomposition temperature of the modified para-aramid paper is >530°C; 3) the tensile strength of the modified para-aramid paper is >60MPa; 4) the interlayer peel strength of the modified para-aramid paper is >150J / m 2 .
[0011] In a second aspect, the present application provides a method for preparing modified para-aramid paper, comprising the following steps:
[0012] S1: providing para-aramid paper substrate;
[0013] S2: using a heterocyclic polyamide solution to impregnate the para-aramid paper substrate to obtain a modified para-aramid paper.
[0014] In some embodiments, step S1 includes:
[0015] S11: dispersing a para-aramid raw material for an aramid paper-based material in water to obtain a para-aramid slurry;
[0016] S12: dehydrating and drying the para-aramid slurry to obtain a para-aramid paper substrate.
[0017] In some embodiments, the step S11 comprises: dispersing the para-aramid raw material in water to obtain a para-aramid slurry having a solid content of 0.05% to 0.5%, wherein the para-aramid raw material comprises at least one of para-aramid staple fibers, para-aramid pulp, para-aramid fibrils or para-aramid nanofibers;
[0018] The step S12 comprises:
[0019] S121: performing vacuum-assisted dehydration on the para-aramid slurry to obtain a para-aramid wet paper-based material, wherein a filter screen with a mesh size of 80 to 300 is used in the vacuum-assisted dehydration;
[0020] S122: Drying the p-aramid wet paper base material at 0° C. to 120° C. to obtain a p-aramid paper substrate.
[0021] In some embodiments, step S2 includes:
[0022] S21: using a diamine monomer and a diacyl chloride monomer to undergo a polymerization reaction in a non-protonic polar solvent containing a solubilizing salt to obtain a heterocyclic polyamide reaction solution, wherein the concentration of the diamine monomer is 0.1 mol / L to 0.5 mol / L, the diamine monomer comprises a first diamine monomer and a second diamine monomer, the first diamine monomer is a heterocyclic diamine, and the second diamine monomer is an aromatic ring diamine; based on the total molar number of the diamine monomers, the molar percentage of the first diamine monomer is 10% to 90%; the diacyl chloride monomer is terephthaloyl chloride and / or isophthaloyl chloride;
[0023] S22: diluting the heterocyclic polyamide reaction solution with a non-protonic polar solvent to obtain a heterocyclic polyamide solution, wherein the rotational viscosity of the heterocyclic polyamide solution is 10 cp·s to 1000 cp·s.
[0024] In some embodiments, the first diamine monomer includes 2-(4-aminophenyl)-5-amino-benzimidazole; the solubilizing salt includes calcium chloride and / or lithium chloride; the polar aprotic solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide; the mass ratio of the solubilizing salt to the polar aprotic solvent is (2 to 10):100.
[0025] In some embodiments, step S2 further includes:
[0026] S23: soaking the para-aramid paper substrate with a heterocyclic polyamide solution, so that the heterocyclic polyamide is dispersed in the pores of the para-aramid paper substrate to form a continuous network reinforcement structure, thereby obtaining a modified para-aramid wet paper-based material;
[0027] S24: washing the modified para-aramid wet paper-based material using a washing liquid;
[0028] S25: drying and calendering the washed modified para-aramid wet paper base material to obtain modified para-aramid paper.
[0029] In some embodiments, the S23 specifically includes:
[0030] The heterocyclic polyamide solution is uniformly coated or sprayed on one surface of the para-aramid paper substrate, and negative pressure filtration is used on the other opposite surface of the para-aramid paper substrate to accelerate the penetration of the heterocyclic polyamide solution in the para-aramid paper substrate, so that the heterocyclic polyamide is dispersed in the pores of the para-aramid paper substrate to form a continuous network reinforcement structure, thereby obtaining a modified para-aramid wet paper-based material, wherein the negative pressure is -0.03MPa to -0.08MPa.
[0031] In a third aspect, the present application further provides a product, including: the modified para-aramid paper according to any embodiment of the first aspect or the modified para-aramid paper prepared by the method described in any embodiment of the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0033] Figure 1 Surface scanning electron microscope (SEM) images of the para-aramid base paper and the modified para-aramid paper prepared in Example 1;
[0034] Figure 2 SEM images of the peeling surfaces (testing interlayer peeling strength) of the para-aramid base paper and the modified para-aramid paper prepared in Example 1;
[0035] Figure 3 These are the thermal weight loss curves of the para-aramid base paper and modified para-aramid paper prepared in Example 1.
[0036] The above drawings have shown clear embodiments of the present application, which will be described in more detail later. These drawings and text descriptions are not intended to limit the scope of the present application in any way, but to illustrate the concept of the present application to those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION
[0037] The various embodiments or implementation schemes in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments.
[0038] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the implementation or examples are included in at least one implementation or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same implementation or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more implementations or examples in a suitable manner.
[0039] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0040] As described in the background technology, although para-aramid has good performance, the existing para-aramid paper has poor uniformity due to the hydrophobic, smooth and highly inert surface of para-aramid fibers, and the bonding force between para-aramid fibers is very weak, and the mechanical properties of para-aramid cannot be effectively exerted.
[0041] In view of the above problems, using a binder to strengthen aramid paper is a feasible solution in principle. Adding binder fibers (fibers that are easy to melt and deform under hot pressing) to aramid paper or using a reinforcing resin to bond it after papermaking can enhance the interfacial adhesion between aramid fibers, better transfer stress, improve the uniformity of paper, reduce the number of pores, and effectively enhance the peel strength of aramid paper. So far, a variety of resins have been used as binders to strengthen aramid paper, including phenolic, epoxy, meta-aramid, polyimide, etc. However, these resins all have some obvious disadvantages: the poor heat resistance and mechanical properties of epoxy and phenolic resins themselves will reduce the performance of aramid paper; although meta-aramid is better than phenolic and epoxy resins, its heat resistance and mechanical properties are still not comparable to para-aramid; although the introduction of polyimide can improve the performance of aramid paper, the high cost of polyimide will limit the application of aramid paper, and the two-step reaction of polyimide (using polyamic acid as a binder) also increases the complexity of the aramid paper preparation process.
[0042] Based on this, the present application provides a modified para-aramid paper and a preparation method and product thereof, wherein the para-aramid paper is reinforced with heterocyclic polyamide to obtain a modified para-aramid paper with good mechanical properties. The technical solution of the present application is described in detail below.
[0043] In a first aspect, the present application provides a modified para-aramid paper, comprising: a para-aramid paper substrate, comprising a fiber non-woven fabric formed by para-aramid fibers entangled with each other or bonded based on non-covalent forces; and a heterocyclic polyamide dispersed in the fiber non-woven fabric of the para-aramid fibers.
[0044] According to the present application, the para-aramid paper substrate mainly includes a fiber non-woven fabric formed by para-aramid fibers entangled with each other or combined based on non-covalent forces, and the heterocyclic polyamide is dispersed in the fiber non-woven fabric to play the role of a binder, thereby enhancing the interfacial bonding force between the para-aramid fibers in the fiber non-woven fabric, so that the stress is better transferred, and the peel strength of the para-aramid paper substrate can be effectively enhanced; since the heterocyclic polyamide also has good mechanical properties, the use of heterocyclic polyamide to modify the para-aramid paper substrate can also improve the tensile strength of the para-aramid paper substrate. In addition, the heterocyclic polyamide has good film-forming properties, and the heterocyclic polyamide and para-aramid have good compatibility, and the interface between the two can be effectively composited, so that the heterocyclic polyamide dispersed in the fiber non-woven fabric of the para-aramid fiber can effectively reduce the porosity of the para-aramid paper substrate, and more significantly improve the uniformity of the para-aramid paper substrate, so that a modified para-aramid paper with good mechanical properties can be obtained, and the better uniformity can also expand the application range of the modified para-aramid paper.
[0045] In addition, since heterocyclic polyamide has good heat resistance, that is, it has a high thermal decomposition temperature, although the thermal decomposition temperature varies slightly depending on the type of monomer used to prepare the heterocyclic polyamide, it is equivalent to the thermal properties of para-aramid. Therefore, using heterocyclic polyamide to modify the para-aramid paper substrate can improve its mechanical properties without affecting the heat and flame retardant properties of the para-aramid paper substrate.
[0046] It should be noted that in the context of the present application, non-covalent forces have a meaning well known in the art, and specifically may include hydrogen bonding forces, van der Waals forces, conjugated forces, and the like.
[0047] In some embodiments, in the modified para-aramid paper, at least part of the molecular chains of the heterocyclic polyamide pass through the pores in the nonwoven fabric of the para-aramid fibers to form a continuous network reinforcement structure.
[0048] In some of the above embodiments, the good permeability of the heterocyclic polyamide solution can be utilized. At the same time, due to the good compatibility between heterocyclic polyamide and para-aramid, part of the molecular chains of the heterocyclic polyamide can pass through the pores in the fiber non-woven fabric of the para-aramid fiber to form a continuous network reinforcement structure, thereby further improving the uniformity of the modified para-aramid paper; in addition, the formation of the continuous network reinforcement structure is more conducive to the transfer of stress of the modified para-aramid paper, thereby further improving the mechanical properties of the modified para-aramid paper.
[0049] In some embodiments, the heterocyclic polyamide is obtained by polymerization of a diamine monomer and a diacyl chloride monomer, wherein the diamine monomer includes a first diamine monomer and a second diamine monomer, the first diamine monomer is a heterocyclic diamine, and the second diamine monomer is an aromatic ring diamine.
[0050] In some of the above embodiments, the heterocyclic polyamide can be obtained by polymerization of a diamine monomer and a diacyl chloride monomer, wherein the diamine monomer includes a first diamine monomer and a second diamine monomer, the first diamine monomer is a heterocyclic diamine, and the second diamine monomer is an aromatic ring diamine. This is because the heterocyclic polyamide obtained by polymerization using a diamine monomer including a heterocyclic diamine has a smaller molecular chain rigidity than the aromatic polyamide obtained by polymerization using a diamine monomer including only an aromatic ring diamine. On the one hand, the heterocyclic polyamide has better solubility, which can reduce the production and processing costs. On the other hand, the heterocyclic polyamide has better film-forming properties, which is more conducive to improving the uniformity of the para-aramid paper base film, and is easier to pass through the pores in the fiber non-woven fabric of the para-aramid fiber to form a continuous network reinforcement structure, so that the mechanical properties of the modified para-aramid paper are better.
[0051] In some embodiments, the modified para-aramid paper satisfies at least one of the following conditions: 1) the air permeability of the modified para-aramid paper is less than 0.001 μm / (Pa·s); 2) the thermal decomposition temperature of the modified para-aramid paper is greater than 530°C (weight loss is more than 10%); 3) the tensile strength of the modified para-aramid paper is greater than 60 MPa; 4) the interlayer peel strength of the modified para-aramid paper is greater than 150 J / m 2 .
[0052] In some of the above examples, the air permeability, thermal decomposition temperature, tensile strength and interlayer peeling strength of the modified para-aramid paper provided by the present application were tested. Among them, the air permeability of the modified para-aramid paper is less than 0.001 μm / (Pa·s), indicating that the heterocyclic polyamide can be filled in the pores in the fiber non-woven fabric of the para-aramid fiber, improving the uniformity of the para-aramid paper, thereby obtaining a modified para-aramid paper with a lower porosity, and thus having better mechanical properties.
[0053] The thermal decomposition temperature of the modified para-aramid paper is greater than 530°C (weight loss of more than 10%), indicating that the heterocyclic polyamide has a heat resistance comparable to that of para-aramid, and the use of heterocyclic polyamide to modify the para-aramid paper will not significantly reduce its heat resistance. Therefore, the modified para-aramid paper provided in the present application has good mechanical properties as well as good heat resistance.
[0054] It should be noted that, in the context of the present application, the thermal decomposition temperature refers to the temperature corresponding to 10% weight loss in the thermal weight loss curve of the material using the thermogravimetric analysis method.
[0055] The tensile strength of modified para-aramid paper is greater than 60MPa and the interlayer peel strength is greater than 150J / m 2 Compared with the tensile strength and interlayer peeling strength of the para-aramid base paper, it has been significantly improved, indicating that the modified para-aramid paper provided in the present application has good mechanical properties.
[0056] In a second aspect, the present application provides a method for preparing modified para-aramid paper, comprising the following steps:
[0057] S1: providing para-aramid paper substrate;
[0058] S2: using a heterocyclic polyamide solution to impregnate a para-aramid paper substrate to obtain a modified para-aramid paper.
[0059] According to the present application, a method for preparing modified para-aramid is provided, wherein a para-aramid paper substrate is infiltrated with a heterocyclic polyamide solution, and since the heterocyclic polyamide has good film-forming properties and good compatibility with para-aramid, the heterocyclic polyamide is dispersed on the para-aramid paper substrate, thereby obtaining modified para-aramid paper. The modified para-aramid paper obtained by the above method has good mechanical properties, and the specific reasons thereof can be found in the description of the modified para-aramid paper in the first aspect above.
[0060] In addition, there is no restriction on the source of the para-aramid paper substrate, and it can be produced using existing processes or directly purchased. The para-aramid paper substrate can then be modified by directly impregnating the para-aramid paper substrate with a heterocyclic polyamide solution. Therefore, this method has a simple process and is suitable for industrial production applications.
[0061] In some embodiments, step S1 includes:
[0062] S11: dispersing a para-aramid raw material for an aramid paper-based material in water to obtain a para-aramid slurry;
[0063] S12: Dehydrating and drying the para-aramid slurry to obtain a para-aramid paper substrate.
[0064] In some of the above embodiments, step S1 is further limited, that is, para-aramid raw materials are used to prepare para-aramid substrates. Since the heterocyclic polyamide solution has good permeability, in the process of preparing the modified para-aramid substrate, there is no need to further improve the production process of the para-aramid paper substrate. Therefore, the above method is used to prepare the modified para-aramid paper. Compared with the existing para-aramid paper production line, it only needs to add a step of infiltrating the heterocyclic polyamide solution, that is, the modified para-aramid paper with good mechanical properties can be obtained, and there is no need to carry out complex upgrading and transformation of the original production line, which can effectively reduce the production cost, thereby being more suitable for industrial production applications.
[0065] In some embodiments, step S11 includes: dispersing a para-aramid raw material in water to obtain a para-aramid slurry with a solid content of 0.05% to 0.5%, wherein the para-aramid raw material includes at least one of para-aramid staple fibers, para-aramid pulp, para-aramid fibrils, or para-aramid nanofibers;
[0066] Step S12 includes:
[0067] S121: performing vacuum-assisted dehydration on the para-aramid slurry to obtain a para-aramid wet paper base material, wherein a filter screen with a mesh size of 80 to 300 is used in the vacuum-assisted dehydration;
[0068] S122: Drying the p-aramid wet paper base material at 0° C. to 120° C. to obtain a p-aramid paper substrate.
[0069] In some of the above embodiments, steps S11 and S12 are further limited, wherein the solid content of the para-aramid pulp can be 0.05% to 0.5%. It can be understood that if the solid content is too low, it may result in an inability to obtain a para-aramid paper substrate with a stable structure, while if the solid content is too high, it may result in poor uniformity of the para-aramid paper substrate, both of which are not conducive to obtaining a para-aramid paper substrate with good quality.
[0070] In addition, the para-aramid raw material may include at least one of para-aramid staple fibers, para-aramid pulp, para-aramid fibrils or para-aramid nanofibers. It is understood that those skilled in the art may select according to actual needs. Among them, the para-aramid staple fibers may be short-cut fibers with a length of 1 mm to 10 mm, preferably 6 mm, which are obtained by straight cutting of para-aramid filaments; and the para-aramid nanofibers may be aqueous dispersions with a diameter of 10 nm to 60 nm prepared by polymerization.
[0071] Preferably, the para-aramid raw material includes 20% to 50% para-aramid staple fibers by weight. It is understandable that the para-aramid staple fibers are more likely to form a stable fiber non-woven fabric, and the fiber non-woven fabric is filled with other raw materials, such as para-aramid pulp, para-aramid fibrils or para-aramid nanofibers, to obtain a para-aramid paper substrate with good uniformity.
[0072] At the same time, in the above embodiment, the conditions for obtaining a para-aramid paper substrate by dehydrating and drying the para-aramid slurry are further limited. The vacuum-assisted dehydration method is used, and a filter screen with a suitable mesh size is used to help improve the uniformity of the para-aramid paper substrate to obtain a para-aramid paper substrate with better mechanical properties.
[0073] In some embodiments, step S2 includes:
[0074] S21: Use diamine monomers and diacyl chloride monomers to carry out polymerization reaction in a non-protonic polar solvent containing a solubilizing salt to obtain a heterocyclic polyamide reaction solution, wherein the concentration of the diamine monomer is 0.1 mol / L to 0.5 mol / L, the diamine monomers include a first diamine monomer and a second diamine monomer, the first diamine monomer is a heterocyclic diamine, and the second diamine monomer is an aromatic ring diamine; based on the total molar number of the diamine monomers, the molar percentage of the first diamine monomer is 10% to 90%; the diacyl chloride monomer is terephthaloyl chloride and / or isophthaloyl chloride.
[0075] S22: diluting the heterocyclic polyamide reaction solution with a non-protonic polar solvent to obtain a heterocyclic polyamide solution, wherein the rotational viscosity of the heterocyclic polyamide solution is 10 cp·s to 1000 cp·s.
[0076] In some of the above embodiments, a preparation method of a heterocyclic polyamide solution is provided. It is understandable that, although heterocyclic polyamide has a lower rigidity of molecular weight than aromatic polyamide, so it has better solubility, but for general heterocyclic polyamide, its solubility is still poor, and the dissolution and dispersion conditions are harsh, so heterocyclic polyamide solution is prepared using directly purchased heterocyclic polyamide, which will increase production costs on the one hand, and on the other hand, if heterocyclic polyamide is unevenly dispersed in the solution, it will affect the film-forming property of heterocyclic polyamide, so the above method can be used to prepare heterocyclic polyamide solution. The heterocyclic polyamide solution prepared by the above copolymerization method can be stably present for a long time, so as to be more suitable for industrial production.
[0077] In the above preparation process, the diamine monomer and the diacyl chloride are subjected to a condensation reaction in a polar aprotic solvent containing a solubilizing salt, which can promote the dissolution of the diamine monomer and the diacyl chloride in the reaction system and make the reaction more complete; the polar aprotic solvent can promote the dispersion and dissolution of the heterocyclic polyamide, and the solubilizing salt can further increase the dissolution of the heterocyclic polyamide, and can improve the stability of the heterocyclic polyamide solution.
[0078] In addition, the concentration of the diamine monomer in the reaction system and the molar percentage of the first diamine monomer in the diamine monomer are further limited, wherein the control of the concentration of the diamine monomer can obtain a heterocyclic polyamide of suitable molecular weight, which is beneficial to improve the film-forming property of the heterocyclic polyamide; in addition, if the content of the first diamine monomer, that is, the heterocyclic diamine, is too high, although the rigidity of the heterocyclic polyamide is further reduced, it will affect the heat resistance of the heterocyclic polyamide. In order to make it comparable to the thermal decomposition temperature of para-aramid, the content of the heterocyclic diamine should not be too high. If the content of the first diamine monomer is too low, the rigidity of the heterocyclic polyamide is too large. On the one hand, the solubility of the heterocyclic polyamide is reduced, and on the other hand, its adhesion and film-forming properties are poor, and it is not easy to be interspersed in the para-aramid fiber non-woven fabric, which is not conducive to forming an interpenetrating network structure, resulting in the deterioration of the mechanical properties of the modified para-aramid paper. Further preferably, based on the total molar number of the diamine monomer, the molar percentage of the first diamine monomer can be 50% to 80%.
[0079] Furthermore, it is necessary to dilute the heterocyclic polyamide reaction solution to obtain a heterocyclic polyamide solution, wherein the rotational viscosity of the heterocyclic polyamide solution should be controlled within an appropriate range. This is because when the rotational viscosity of the heterocyclic polyamide solution is too high, the permeability of the heterocyclic polyamide solution may deteriorate, which is not conducive to forming a continuous network reinforcement structure, while increasing the difficulty of processing and the production cost; if the rotational viscosity of the heterocyclic polyamide solution is too low, the film-forming and bonding properties of the heterocyclic polyamide solution may be poor, which is not conducive to dispersion in the fiber nonwoven fabric composed of para-aramid fibers, and it is impossible to obtain a modified para-aramid paper with good mechanical properties.
[0080] It is understood that in the examples of the present application, the molar ratio of the diacyl chloride monomer to the diamine monomer is (0.9 to 1.1): 1; preferably, the molar ratio is (0.99 to 1.01): 1, and more preferably, (0.999 to 1.001): 1. The closer the molar ratio is to 1, the easier it is to prepare a heterocyclic polyamide with a higher molecular weight.
[0081] In some embodiments, step S21 is performed under heating and stirring conditions, wherein the heating temperature may be 50° C. to 100° C., the stirring rate may be 300 rpm to 2000 rpm, and the polymerization reaction time may be 20 min to 120 min.
[0082] In some embodiments, the second diamine monomer includes at least one of p-phenylenediamine, m-phenylenediamine, 5-chloro-p-phenylenediamine, 2,5-dichloro-p-phenylenediamine, 3,4-diaminodiphenyl ether, 4,4-diaminodiphenyl ether and 2,2'-bis(trifluoromethyl)diaminobiphenyl. The second diamine monomer can be any of the above aromatic diamines, and those skilled in the art can select at least one of the above compounds as the second diamine monomer according to actual needs.
[0083] In some embodiments, the first diamine monomer includes 2-(4-aminophenyl)-5-amino-benzimidazole; the solubilizing salt includes calcium chloride and / or lithium chloride; the polar aprotic solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide; the mass ratio of the solubilizing salt to the polar aprotic solvent is (2 to 10):100.
[0084] In some of the above embodiments, the first diamine monomer may include 2-(4-aminophenyl)-5-amino-benzimidazole. 2-(4-aminophenyl)-5-amino-benzimidazole can significantly reduce the rigidity of the heterocyclic polyamide molecular chain and greatly improve its solubility, so that the heterocyclic polyamide can more easily penetrate into the pores of the para-aramid fiber non-woven fabric to form a continuous network reinforcement structure, thereby improving the mechanical properties of the modified polyamide.
[0085] At the same time, the compounds that can be included in the solubilizing salt and the polar aprotic solvent are also limited. This is because calcium ions and / or lithium ions can form a coordination effect with the amide bond, play an isolating role between the molecular chains, hinder the polymerization of the molecular chains due to hydrogen bonds and conjugation, and improve the solubility of the heterocyclic polyamide; N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide are commonly used polar aprotic solvents in the field, which can promote the dispersion and solution of heterocyclic polyamides. Those skilled in the art can choose according to needs.
[0086] Furthermore, the mass ratio of the solubilizing salt to the polar aprotic solvent can be (2 to 10): 100, in which case the solubilizing salt can be fully dissolved in the polar aprotic solvent to promote the dissolution of the heterocyclic polyamide. If the amount of the solubilizing salt added is too large, it cannot be fully dissolved in the polar aprotic solvent.
[0087] In some embodiments, step S2 further includes:
[0088] S23: soaking the para-aramid paper substrate with the heterocyclic polyamide solution, so that the heterocyclic polyamide is dispersed in the pores of the para-aramid paper substrate to form a continuous network reinforcement structure, thereby obtaining a modified para-aramid wet paper-based material;
[0089] S24: washing the modified para-aramid wet paper-based material using a washing liquid;
[0090] S25: drying and calendering the washed modified para-aramid wet paper base material to obtain modified para-aramid paper.
[0091] In some of the above embodiments, step S2 is further limited. Since the heterocyclic polyamide solution is obtained by polymerization and dilution, the heterocyclic polyamide solution contains polar aprotic solvents and dissolving salts. After the heterocyclic polyamide solution is used to infiltrate the para-aramid paper substrate and the heterocyclic polyamide is dispersed in the pores of the para-aramid paper substrate to form a continuous network reinforcement structure, it is necessary to use a washing liquid to wash the modified para-aramid wet paper base material to remove the polar aprotic solvent and the dissolving salt. Finally, it is dried and calendered to obtain the modified para-aramid paper with good mechanical properties.
[0092] In some embodiments, the washing liquid includes at least one of water, methanol or ethanol. The washing liquid is volatile, not easy to remain, has good solubility for the solubilizing salt, and is miscible with the polar aprotic solvent, and has a good washing effect.
[0093] In some embodiments, in step S25, the drying temperature may be 60°C to 150°C, and the drying temperature may be adjusted according to the components of the washing liquid.
[0094] In some embodiments, the calendering condition may be 200° C. to 300° C., and the pressure may be 5 MPa to 15 MPa. Under such conditions, the uniformity of the modified para-aramid paper may be improved, and the mechanical properties of the modified para-aramid paper may be improved.
[0095] In some embodiments, S23 specifically includes:
[0096] The heterocyclic polyamide solution is uniformly coated or sprayed on one surface of a para-aramid paper substrate, and negative pressure filtration is used on the other opposite surface of the para-aramid paper substrate to accelerate the penetration of the heterocyclic polyamide solution in the para-aramid paper substrate, so that the heterocyclic polyamide is dispersed in the pores of the para-aramid paper substrate to form a continuous network reinforcement structure, and a modified para-aramid wet paper-based material is obtained, wherein the negative pressure is -0.03MPa to -0.08MPa.
[0097] In some of the above embodiments, the manner in which the heterocyclic polyamide solution is infiltrated into the para-aramid paper substrate is further limited. The heterocyclic polyamide solution can be uniformly coated or sprayed on one surface of the para-aramid paper substrate, and negative pressure filtration is used on the other surface of the para-aramid paper substrate. This can accelerate the penetration of the heterocyclic polyamide solution into the para-aramid paper substrate, thereby better forming a continuous network reinforcement structure and improving the mechanical properties of the modified para-aramid paper.
[0098] In addition, the negative pressure value is further limited. It can be understood that the greater the negative pressure, the greater the penetration rate. However, if the penetration rate is too large and the infiltration time is short, it will be unfavorable to form a continuous network reinforcement structure. If the negative pressure is too small and the penetration rate is too slow, it will affect the production efficiency. Therefore, the negative pressure can be controlled at -0.03MPa to -0.08MPa.
[0099] In some embodiments, step S23 may further include: rolling the modified para-aramid wet paper-based material to further homogenize (or remove) the heterocyclic polyamide solution in the aramid paper.
[0100] As an example, in actual production, the para-aramid paper substrate can be laid flat on the filter cloth, and then the heterocyclic polyamide solution can be evenly coated or sprayed onto the upper surface of the para-aramid paper substrate; negative pressure filtration is used on the lower surface of the filter cloth to accelerate the penetration of the heterocyclic polyamide solution into the aramid paper; the content of the heterocyclic polyamide solution in the para-aramid paper is controlled by negative pressure and the moving speed of the filter cloth; the heterocyclic polyamide solution extracted by negative pressure is transported to the heterocyclic polyamide solution storage tank for recycling; the aramid paper after impregnation is further homogenized (or removed) by the counter-pressure roller; and then immersed in the washing liquid to wash and remove the solvent and solubilizing salt in the heterocyclic polyamide. Then continuous drying and calendering can obtain the enhanced para-aramid paper.
[0101] In a third aspect, the present application further provides a product, including: the modified para-aramid paper according to any embodiment of the first aspect or the modified para-aramid paper prepared by the method according to any embodiment of the second aspect.
[0102] According to the present application, since the product includes the modified para-aramid paper according to any embodiment of the first aspect or the modified para-aramid paper prepared by the method according to any embodiment of the second aspect, it has the beneficial effects of the first aspect or the second aspect.
[0103] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0104] The properties of the para-aramid base paper and the modified para-aramid paper obtained in the following examples and comparative examples were tested, and the testing method was as follows:
[0105] 1. Tensile strength: mechanical universal testing machine, test standard GB / T 12914-91, tensile rate 5mm / min; spline width 10mm, gauge length 30mm;
[0106] 2. Air permeability: Gurley method. Test standard GB / T 458-2008;
[0107] 3. Interlayer peel strength: Test standard GB / T 26203-2010 Determination of internal bonding strength of paper and paperboard (Scott type);
[0108] 4. Thermal decomposition temperature: thermal gravimetric method. Test standard ASTM E2402-2005.
[0109] Example 1
[0110] (1) Preparation of para-aramid base paper: para-aramid staple fibers with a length of 6 mm and para-aramid nanofibers with an average diameter of 60 nm are dispersed in water to prepare para-aramid slurry. The solid content of the para-aramid slurry is 0.02%, of which the content of para-aramid staple fibers is 60wt%, and the content of para-aramid nanofibers is 40wt%. The prepared para-aramid slurry is dehydrated on a continuous papermaking machine by vacuum-assisted dehydration to prepare para-aramid wet paper, and a 200-mesh filter screen is selected for vacuum-assisted dehydration. After dehydration, the para-aramid base paper is prepared by continuous wet paper peeling, drying, and winding. The prepared para-aramid base paper has a thickness of 50μm and a surface density of 56g / cm 2 .
[0111] (2) Preparation of heterocyclic polyamide solution: Under nitrogen protection and stirring conditions, in a polymerization kettle with a temperature control jacket, 35 kg of dried dissolving salt lithium chloride was added to 1000 kg of N,N-dimethylacetamide with a water content of 80 ppm, and the mixture was heated to 80°C to completely dissolve the lithium chloride. Then, cold water was passed through the polymerization kettle to cool the material to 15°C to obtain a first solution. A diamine monomer consisting of 10.8 kg of p-phenylenediamine and 22.4 kg of 2-(4-aminophenyl)-5-aminobenzimidazole (M3) was added to the first solution and stirred to dissolve. The molar ratio of p-phenylenediamine to M3 in the diamine monomer was 1:1, and the molar concentration in the first solution was 0.2 mol / L. After the diamine monomer was dissolved, the material in the polymerization kettle was cooled to 0°C, and the stirring speed was set to 500 rpm to start the polymerization reaction. 40.88 kg of terephthaloyl chloride solid powder (or 95°C melt) was added to the polymerization kettle in four times, each time with an interval of 10 minutes, and the four addition amounts accounted for 50%, 40%, 9%, and 1% of the total amount respectively. After the addition was completed, the molar ratio of terephthaloyl chloride and diamine monomer was 1.007:1. The reaction was continued for 30 minutes. After the polymerization was completed, 3000 kg of N,N-dimethylacetamide was added under stirring conditions to make the polymerization liquid into a clear and transparent solution. The rotational viscosity of the solution was 234 cp·s, and a heterocyclic polyamide solution was obtained, which was placed in a storage tank for standby use.
[0112] (3) Preparation of heterocyclic polyamide modified para-aramid paper: The para-aramid base paper is laid flat on a 200-mesh filter cloth, and then the heterocyclic polyamide solution is continuously and evenly sprayed onto the upper surface of the para-aramid paper using a booster pump; a negative pressure filtration with a vacuum degree of -0.05 MPa is used on the lower surface of the filter cloth to accelerate the penetration of the heterocyclic polyamide solution into the aramid paper; the filter cloth moving speed is controlled to be 10 m / min; the heterocyclic polyamide solution extracted by the negative pressure is transported to the heterocyclic polyamide solution storage tank for recycling; the aramid paper after impregnation is further homogenized (or removed) by a counter-pressing roller, and the counter-pressing roller pressure is 0.01 MPa; then the aramid paper is immersed in water for continuous countercurrent washing to remove the solvent and solubilizing salt in the heterocyclic polyamide. Then, the modified para-aramid paper is obtained by continuous drying and calendering. The drying temperature is 120°C, the setting temperature of the calender is 260°C, and the pressure is 12 MPa. The prepared modified para-aramid paper has a thickness of 47 μm and a surface density of 50 g / m 2 The heterocyclic polyamide content was calculated by weighing and was 1.8%. Other performance test results are shown in Table 1.
[0113] In addition, the surfaces of the para-aramid base paper and the modified para-aramid paper and the interlayer peeling surface were observed using an electron scanning microscope. Figure 1 The SEM images of the surface of para-aramid base paper (left) and modified para-aramid paper (right) are shown in the figure. It can be seen from the figure that the porosity of the modified para-aramid paper is significantly lower than that of the para-aramid base paper, and it has better uniformity, indicating that the heterocyclic polyamide can be filled in the pores of the para-aramid base paper; Figure 2 The SEM images of the interlayer peeling surface of the para-aramid base paper (left) and the modified para-aramid paper (right) are shown in the figure. It can be seen from the figure that the porosity of the interlayer peeling surface of the modified para-aramid paper is significantly lower than that of the para-aramid base paper, indicating that the heterocyclic polyamide solution has good permeability and also has a good bonding effect on the inside of the base paper, thereby improving the mechanical properties of the para-aramid paper.
[0114] The above para-aramid base paper and modified para-aramid paper were subjected to thermogravimetric analysis. Figure 3 The thermal weight loss curves of para-aramid base paper and modified para-aramid paper are shown. It can be seen from the figure that the thermal weight loss curves of the two are not much different, indicating that the use of heterocyclic polyamide to modify the para-aramid base paper does not significantly reduce the heat resistance of the para-aramid base paper.
[0115] Example 2
[0116] (1) Preparation of para-aramid base paper: para-aramid staple fibers with a length of 6 mm and para-aramid pulp are dispersed together in water to prepare para-aramid slurry. The solid content of the para-aramid slurry is 0.03%, of which the content of para-aramid staple fibers and pulp is 50wt% each. The prepared para-aramid slurry is dehydrated on a continuous papermaking machine by vacuum-assisted dehydration to prepare para-aramid wet paper, and a 200-mesh filter screen is selected for vacuum-assisted dehydration. After dehydration, the para-aramid base paper is prepared by continuous wet paper peeling, drying, and winding. The prepared para-aramid base paper has a thickness of 52μm and a surface density of 54g / cm 2 .
[0117] (2) Preparation of heterocyclic polyamide solution: Under nitrogen protection and stirring conditions, in a polymerization kettle with a temperature control jacket, 30 kg of dried dissolving salt calcium chloride was added to 1000 kg of N-methylpyrrolidone with a water content of 50 ppm, and the mixture was heated to 80°C to completely dissolve the calcium chloride. Then, cold water was passed through the polymerization kettle to cool the material to 15°C to obtain a first solution. A diamine monomer consisting of 10.8 kg of m-phenylenediamine and 22.4 kg of 2-(4-aminophenyl)-5-aminobenzimidazole (M3) was added to the first solution and stirred to dissolve. The molar ratio of m-phenylenediamine to M3 in the diamine monomer was 1:1, and the molar concentration in the first solution was 0.2 mol / L. After the diamine monomer was dissolved, the material in the polymerization kettle was cooled to 0°C, and the stirring speed was set to 500 rpm to start the polymerization reaction. 40.88 kg of solid powder of isophthaloyl chloride (or melt at 60°C) was added to the polymerization kettle three times, each time with an interval of 10 minutes, and the three addition amounts accounted for 50%, 40%, and 10% of the total amount respectively. After the addition was completed, the molar ratio of isophthaloyl chloride to diamine monomer was 1.007:1. The reaction was continued for 60 minutes. After the polymerization was completed, 1000 kg of N-methylpyrrolidone was added under stirring conditions to make the polymerization liquid become a clear and transparent solution. The rotational viscosity of the solution was 85 cp·s, and a heterocyclic polyamide solution was obtained, which was placed in a storage tank for standby use.
[0118] (3) Preparation of heterocyclic polyamide modified para-aramid paper: The para-aramid base paper is laid flat on a 200-mesh filter cloth, and then the heterocyclic polyamide solution is continuously and evenly sprayed onto the upper surface of the para-aramid paper using a booster pump; a negative pressure filtration with a vacuum degree of -0.03 MPa is used on the lower surface of the filter cloth to accelerate the penetration of the heterocyclic polyamide solution into the aramid paper; the filter cloth moving speed is controlled to be 20 m / min; the heterocyclic polyamide solution extracted by the negative pressure is transported to the heterocyclic polyamide solution storage tank for recycling; the aramid paper after impregnation is further homogenized (or removed) by a counter-pressing roller, and the counter-pressing roller pressure is 0.01 MPa; then the aramid paper is immersed in water for continuous countercurrent washing to remove the solvent and solubilizing salt in the heterocyclic polyamide. Then, the modified para-aramid paper is obtained by continuous drying and calendering. The drying temperature is 120°C, the setting temperature of the calender is 260°C, and the pressure is 10 MPa. The prepared modified para-aramid paper has a thickness of 50 μm and a surface density of 55 g / cm 2 The heterocyclic polyamide content was calculated to be 0.8%. Other performance test results are shown in Table 1.
[0119] Example 3
[0120] (1) Preparation of para-aramid base paper: para-aramid staple fibers and para-aramid fibrils with a length of 6 mm are dispersed together in water to prepare para-aramid slurry. The solid content of the para-aramid slurry is 0.02%, of which the content of para-aramid staple fibers and fibrils is 50wt%. The prepared para-aramid slurry is dehydrated on a continuous papermaking machine by vacuum-assisted dehydration to prepare para-aramid wet paper, and a 200-mesh filter screen is selected for vacuum-assisted dehydration. After dehydration, the para-aramid base paper is prepared by continuous wet paper peeling, drying, and winding. The prepared para-aramid base paper has a thickness of 50μm and a surface density of 54g / cm 2 .
[0121] (2) Preparation of heterocyclic polyamide solution: Under nitrogen protection and stirring conditions, in a polymerization kettle with a temperature control jacket, 80 kg of dried dissolving salt calcium chloride was added to 1000 kg of N-methylpyrrolidone with a water content of 80 ppm, and the mixture was heated to 80°C to completely dissolve the calcium chloride. Then, cold water was passed through the polymerization kettle to cool the material to 15°C to obtain a first solution. A diamine monomer consisting of 14.25 kg of 5-chloro-p-phenylenediamine and 44.8 kg of 2-(4-aminophenyl)-5-aminobenzimidazole (M3) was added to the first solution and stirred to dissolve. The molar ratio of 5-chloro-p-phenylenediamine to M3 in the diamine monomer was 1:2, and the molar concentration in the first solution was 0.3 mol / L. After the diamine monomer was dissolved, the material in the polymerization kettle was cooled to 0°C, and then the stirring speed was set to 500 rpm to start the polymerization reaction. 61.20 kg of terephthaloyl chloride solid powder (or 95°C melt) was added to the polymerization kettle three times, each time with an interval of 10 minutes, and the three addition amounts accounted for 50%, 40%, and 10% of the total amount respectively. After the addition was completed, the molar ratio of isophthaloyl chloride and diamine monomer was 1.005:1. The reaction was continued for 90 minutes. After the polymerization was completed, 2000 kg of N-methylpyrrolidone was added under stirring conditions to make the polymerization liquid into a clear and transparent solution. The rotational viscosity of the solution was 560 cp·s, and a heterocyclic polyamide solution was obtained, which was placed in a storage tank for standby use.
[0122] (3) Preparation of heterocyclic polyamide modified para-aramid paper: The para-aramid base paper is laid flat on a 200-mesh filter cloth, and then the heterocyclic polyamide solution is continuously and evenly sprayed onto the upper surface of the para-aramid paper using a booster pump; a negative pressure filtration with a vacuum degree of -0.07 MPa is used on the lower surface of the filter cloth to accelerate the penetration of the heterocyclic polyamide solution into the aramid paper; the filter cloth movement rate is controlled to be 5 m / min; the heterocyclic polyamide solution extracted by the negative pressure is transported to the heterocyclic polyamide solution storage tank for recycling; the aramid paper after impregnation is further homogenized (or removed) by a counter-pressing roller, and the counter-pressing roller pressure is 0.03 MPa; then the aramid paper is immersed in water for continuous countercurrent washing to remove the solvent and solubilizing salt in the heterocyclic polyamide. Then, the modified para-aramid paper is obtained by continuous drying and calendering. The drying temperature is 150°C, the setting temperature of the calender is 280°C, and the pressure is 15 MPa. The prepared modified para-aramid paper has a thickness of 48 μm and a surface density of 55 g / cm 2 The heterocyclic polyamide content was calculated to be 1.6%. Other performance test results are shown in Table 1.
[0123] Example 4
[0124] (1) Preparation of para-aramid base paper: para-aramid staple fibers and para-aramid fibrils with a length of 6 mm are dispersed together in water to prepare para-aramid slurry. The solid content of the para-aramid slurry is 0.02%, of which the content of para-aramid staple fibers and fibrils is 50wt%. The prepared para-aramid slurry is dehydrated on a continuous papermaking machine by vacuum-assisted dehydration to prepare para-aramid wet paper, and a 200-mesh filter screen is selected for vacuum-assisted dehydration. After dehydration, the para-aramid base paper is prepared by continuous wet paper peeling, drying, and winding. The prepared para-aramid base paper has a thickness of 50μm and a surface density of 53g / cm 2 .
[0125] (2) Preparation of heterocyclic polyamide solution: Under nitrogen protection and stirring conditions, in a polymerization kettle with a temperature control jacket, 35 kg of dried dissolving salt lithium chloride was added to 1000 kg of N,N-dimethylformamide with a water content of 70 ppm, and the mixture was heated to 60°C to completely dissolve the lithium chloride. Then, the materials in the polymerization kettle were cooled to 15°C by passing cold water to obtain a first solution. A diamine monomer composed of 10.12 kg of 3,4-diaminodiphenyl ether and 22.4 kg of 2-(4-aminophenyl)-5-aminobenzimidazole (M3) was added to the first solution and stirred to dissolve. The molar ratio of 3,4-diaminodiphenyl ether to M3 in the diamine monomer was 1:2, and the molar concentration in the first solution was 0.15 mol / L. After the diamine monomer was dissolved, the materials in the polymerization kettle were cooled to 0°C, and the stirring speed was set to 500 rpm to start the polymerization reaction. 30.6 kg of terephthaloyl chloride solid powder (or 95°C melt) was added to the polymerization kettle three times, each time with an interval of 10 minutes, and the three addition amounts accounted for 50%, 40%, and 10% of the total amount respectively. After the addition was completed, the molar ratio of isophthaloyl chloride and diamine monomer was 1.005:1. The reaction was continued for 60 minutes. After the polymerization was completed, 1000 kg of N,N-dimethylformamide was added under stirring conditions to make the polymerization liquid into a clear and transparent solution. The rotational viscosity of the solution was 430 cp·s, and a heterocyclic polyamide solution was obtained, which was placed in a storage tank for standby use.
[0126] (3) Preparation of heterocyclic polyamide modified para-aramid paper: The para-aramid base paper is laid flat on a 200-mesh filter cloth, and then the heterocyclic polyamide solution is continuously and evenly sprayed onto the upper surface of the para-aramid paper using a booster pump; a negative pressure filtration with a vacuum degree of -0.05 MPa is used on the lower surface of the filter cloth to accelerate the penetration of the heterocyclic polyamide solution into the aramid paper; the filter cloth moving speed is controlled to be 10 m / min; the heterocyclic polyamide solution extracted by the negative pressure is transported to the heterocyclic polyamide solution storage tank for recycling; the aramid paper after impregnation is further homogenized (or removed) by a counter-pressing roller, and the counter-pressing roller pressure is 0.02 MPa; then the aramid paper is immersed in water for continuous countercurrent washing to remove the solvent and solubilizing salt in the heterocyclic polyamide. Then, the modified para-aramid paper is obtained by continuous drying and calendering. The drying temperature is 120°C, the setting temperature of the calender is 250°C, and the pressure is 10 MPa. The prepared modified para-aramid paper has a thickness of 47 μm and a surface density of 57 g / cm 2 The heterocyclic polyamide content was calculated to be 2.0%. Other performance test results are shown in Table 1.
[0127] Comparative Example 1
[0128] In order to compare the reinforcing effect of heterocyclic aramid, the para-aramid base paper was prepared by the same steps as in Example 1, and the same calendering steps as in Example 1 were used to improve the mechanical properties of the para-aramid base paper.
[0129] (1) Preparation of para-aramid base paper: para-aramid staple fibers with a length of 6 mm and para-aramid nanofibers with an average diameter of 60 nm are dispersed in water to prepare para-aramid slurry. The solid content of the para-aramid slurry is 0.02%, of which the content of para-aramid staple fibers is 60wt% and the content of para-aramid nanofibers is 40wt%. The prepared para-aramid slurry is dehydrated on a continuous papermaking machine by vacuum-assisted dehydration to prepare para-aramid wet paper, and a 200-mesh filter screen is selected for vacuum-assisted dehydration. After dehydration, the para-aramid calendered base paper is prepared by continuous wet paper peeling, drying, calendering and winding. The drying temperature of the para-aramid base paper is 120°C, the setting temperature of the calender is 260°C, and the pressure is 12MPa. The prepared aramid calendered paper has a thickness of 45μm and a surface density of 62g / cm 2 Other performance test results are shown in Table 1.
[0130] Table 1
[0131]
[0132] According to the results in Table 1, compared with Comparative Example 1, Example 1 has significantly improved tensile strength and interlayer peeling strength, and significantly reduced air permeability. At the same time, the thermal decomposition temperature of the modified para-aramid paper is equivalent to that of Comparative Example 1, meeting the requirements of heat resistance. The reason may be that the para-aramid paper substrate is modified by using heterocyclic polyamide, which has good film-forming properties and can be dispersed in the fiber web fiber non-woven fabric of para-aramid fiber. The heterocyclic polyamide can enhance the interfacial bonding between the para-aramid fibers, thereby better transferring stress, and can greatly reduce the porosity of the para-aramid paper (i.e., the air permeability is reduced), thereby significantly improving the uniformity of the para-aramid paper, so that the modified para-aramid paper has higher tensile strength and interlayer peeling strength, and a modified para-aramid paper with good mechanical properties is obtained.
[0133] By comparing the various embodiments, it can be seen that modified para-aramid paper with different properties can be obtained by changing the preparation process conditions or raw materials. However, compared with the para-aramid base paper, the tensile strength and interlayer peeling strength are significantly improved, and the air permeability value is significantly reduced. At the same time, the thermal decomposition temperature of the modified para-aramid paper is not much different from that of the para-aramid base paper, and can still meet the heat resistance requirements.
[0134] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A modified para-aramid paper, characterized in that: include: A para-aramid paper substrate, comprising a fiber nonwoven fabric formed by para-aramid fibers entangled with each other or bonded based on non-covalent forces; and a heterocyclic polyamide dispersed in the fiber nonwoven fabric of the para-aramid fiber; The heterocyclic polyamide is obtained by polymerization of a diamine monomer and a diacyl chloride monomer. The diamine monomer includes a first diamine monomer and a second diamine monomer, the first diamine monomer is a heterocyclic diamine, and the second diamine monomer is an aromatic ring diamine; The diacid chloride monomer is terephthaloyl chloride and / or isophthaloyl chloride.
2. The modified para-aramid paper according to claim 1, characterized in that: At least part of the molecular chains of the heterocyclic polyamide pass through the pores in the fiber nonwoven fabric of the para-aramid fiber to form a continuous network reinforcement structure.
3. The modified para-aramid paper according to claim 1, characterized in that: The modified para-aramid paper satisfies at least one of the following conditions: 1) The air permeability of the modified para-aramid paper is < 0.001 μm / (Pa•s); 2) The thermal decomposition temperature of the modified para-aramid paper is greater than 530°C; 3) The tensile strength of the modified para-aramid paper is >60MPa; 4) The interlayer peel strength of the modified para-aramid paper is >150 J / m 2 .
4. A method for preparing modified para-aramid paper, characterized in that: The following steps are involved: S1: providing para-aramid paper substrate; S2: using a diamine monomer and a diacyl chloride monomer to undergo a polymerization reaction in a non-protonic polar solvent containing a solubilizing salt to obtain a heterocyclic polyamide reaction solution; The diacid chloride monomer is terephthaloyl chloride and / or isophthaloyl chloride; The diamine monomer includes a first diamine monomer and a second diamine monomer, the first diamine monomer is a heterocyclic diamine, and the second diamine monomer is an aromatic ring diamine; The para-aramid paper substrate is impregnated with a heterocyclic polyamide solution to obtain modified para-aramid paper.
5. The method according to claim 4, characterized in that The step S1 comprises: S11: dispersing a para-aramid raw material for an aramid paper-based material in water to obtain a para-aramid slurry; S12: dehydrating and drying the para-aramid slurry to obtain a para-aramid paper substrate.
6. The method according to claim 5, characterized in that The step S11 comprises: dispersing the para-aramid raw material in water to obtain a para-aramid slurry having a solid content of 0.05% to 0.5%, wherein the para-aramid raw material comprises at least one of para-aramid staple fibers, para-aramid pulp, para-aramid fibrids or para-aramid nanofibers; The step S12 comprises: S121: performing vacuum-assisted dehydration on the para-aramid slurry to obtain a para-aramid wet paper-based material, wherein a filter screen with a mesh size of 80 to 300 is used in the vacuum-assisted dehydration; S122: Drying the p-aramid wet paper base material at 0° C. to 120° C. to obtain a p-aramid paper substrate.
7. The method according to claim 4, characterized in that The concentration of the diamine monomer is 0.1 mol / L to 0.5 mol / L; based on the total moles of the diamine monomer, the mole percentage of the first diamine monomer is 10% to 90%; S22: diluting the heterocyclic polyamide reaction solution with a non-protonic polar solvent to obtain a heterocyclic polyamide solution, wherein: The rotational viscosity of the heterocyclic polyamide solution is 10 cp·s to 1000 cp·s.
8. The method according to claim 7, characterized in that The first diamine monomer includes 2-(4-aminophenyl)-5-amino-benzimidazole; The dissolution-advantage salt includes calcium chloride and / or lithium chloride; The polar aprotic solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide; The mass ratio of the solubilizing salt to the polar aprotic solvent is (2 to 10):
100.
9. The method according to claim 7 or 8, characterized in that: The step S2 further comprises: S23: soaking the para-aramid paper substrate with a heterocyclic polyamide solution, so that the heterocyclic polyamide is dispersed in the pores of the para-aramid paper substrate to form a continuous network reinforcement structure, thereby obtaining a modified para-aramid wet paper-based material; S24: washing the modified para-aramid wet paper-based material using a washing liquid; S25: drying and calendering the washed modified para-aramid wet paper base material to obtain modified para-aramid paper.
10. The method according to claim 9, characterized in that The S23 specifically includes: The heterocyclic polyamide solution is uniformly coated or sprayed on one surface of the para-aramid paper substrate, and negative pressure filtration is used on the other surface of the para-aramid paper substrate to accelerate the penetration of the heterocyclic polyamide solution in the para-aramid paper substrate, so that the heterocyclic polyamide is dispersed in the pores of the para-aramid paper substrate to form a continuous network reinforcement structure, thereby obtaining a modified para-aramid wet paper-based material, wherein: The negative pressure is -0.03MPa to -0.08MPa.
11. A product, characterized in that include: The modified para-aramid paper according to claims 1 to 3 or the modified para-aramid paper prepared by the method according to any one of claims 4 to 10.
Citation Information
Patent Citations
Preparation method of heterocyclic aramid paper
CN111235943A
Porous sheet
JP2020111843A
Resin solution for the surface treatment of polymers
US5817416A